The Analysis of Exchange Rate Pass-Through in Indonesia - ., Karsinah; Wisika Prajanti, Sucihatiningsih Dian; ., Widiyanto; Malisa , Nor (KnE Social Sciences, 2019)
The aims of this research are to identify and analyze the exchange rate pass through towards domestic price in Indonesia. The aforementioned objective is reﬂected through the short-term and long-term inﬂuence variable, inﬂation ﬂuctuation response due to other macroeconomic shock variable, which then reveals the characteristics of pass-through degree in Indonesia. The data used on this research was the quarter time series data from 1997 Q3 until 2017Q4. The variable used in this research were Consumer Price Index, Rupiah exchange value per Dollar, Import Price Index and SBI Interest Rate. The resource of the data variable were from Bank Indonesia and International Monetary Fund (IMF). The method being employed was Vector Error Correction Model (VECM). The result of the research shows that in the long-term and short-term period, all variable inﬂuences inﬂation by a different lag. Moreover, the impulse response function assessment reveals that shock variable of import price index receives a positive response by consumer price index. The result of variance decomposition assessment also concludes that the import price index has the biggest contribution. Keywords: Inflation, Exchange Value, Shock, VECM